In vitro phosphorylation as tool for modification of silk and keratin fibrous materials - Volkov, Vadim (2016)
An overview is given of the recent work on in vitro enzymatic phosphorylation of silk fibroin and human hair keratin. Opposing to many chemical "conventional" approaches, enzymatic phosphorylation is in fact a mild reaction and the treatment falls within "green chemistry" approach. Silk and keratin are not phosphorylated in vivo, but in vitro. This enzyme-driven modification is a major technological breakthrough. Harsh chemical chemicals are avoided, and mild conditions make enzymatic phosphorylation a real "green chemistry" approach. The current communication presents a novel approach stating that enzyme phosphorylation may be used as a tool to modify the surface charge of biocompatible materials such as keratin and silk.